The Effect of Work Flexibility on the Performance of Female Workers in the MSME Sector in Pontianak City with Work-Life Balance as a Mediating Variable - Magdalena Melen; Sunardi Ginting (Universitas KH. Abdul Chalim Mojokerto, 2026)
This investigation attempts to look into the effect of work flexibility on the performance of female workers in the MSME sector in Pontianak City, utilizing work-life balance as a mediating variable. The research adopted a quantitative approaches with a survey method. Data was gathered from female woekers working in MSMEs Pontianak City. The findings show that work adaptability has a positive and significant impact on work-life balance, work-life balance has a positive and significant impact on worker productivity, job adaptability has a positive and significant impact on worker productivity, and work-life balance is capable to partially mediate the connection on job adaptability or worker productivity. These findings indicate that providing flexible work arrangements can improve the ability of female workers to balance professional and personal responsibilities, thus impacting overall work performance.